2005
DOI: 10.1002/ajmg.a.30388
|View full text |Cite
|
Sign up to set email alerts
|

Novelc-KIT germline mutation in a family with gastrointestinal stromal tumors and cutaneous hyperpigmentation

Abstract: Mutations in the c-KIT gene have been identified in many sporadic and familial cases of gastrointestinal stromal tumor (GIST). We report a familial case of GIST with cutaneous hyperpigmentation associated with a novel germline mutation in the c-KIT gene. Screening for mutations in exon 11 of the c-KIT gene in genomic DNA from tumors and peripheral blood of the members of a family with GISTs was undertaken by direct genomic sequencing. Tumors from GIST patients were analyzed histologically and immunohistochemic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
40
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(45 citation statements)
references
References 22 publications
3
40
2
Order By: Relevance
“…The proband showed ICC hyperplasia, which is nearly always observed in patients with familial and multiple GISTs. Although hyperpigmentation is often seen and mast cell tumor is sometimes seen in previously reported patients with exon 11 germline c-kit gene mutation, 30,33,34,[36][37][38]44,48 the present patient and her son, a possible carrier, did not show those phenotypes. Dysphagia is also a symptom that is often seen in exon 17 germline c-kit gene mutation, 35,42 but is rarely seen in exon 11 germline ones.…”
Section: Familal Gists With Kit-tyr553cyscontrasting
confidence: 75%
See 2 more Smart Citations
“…The proband showed ICC hyperplasia, which is nearly always observed in patients with familial and multiple GISTs. Although hyperpigmentation is often seen and mast cell tumor is sometimes seen in previously reported patients with exon 11 germline c-kit gene mutation, 30,33,34,[36][37][38]44,48 the present patient and her son, a possible carrier, did not show those phenotypes. Dysphagia is also a symptom that is often seen in exon 17 germline c-kit gene mutation, 35,42 but is rarely seen in exon 11 germline ones.…”
Section: Familal Gists With Kit-tyr553cyscontrasting
confidence: 75%
“…30,31,33,34,[36][37][38][39][40]43,44,46,49 KIT-Val559Ala mutation is the most frequent type, which has been detected in five families. 33,34,38,39,49 Recently, we found a germline mutation at exon 11, KIT-Tyr553Cys, in a 68-yearold woman with multiple GISTs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In GIST kindreds, tumor nodules are often contiguous with areas of hyperplastic ICCs on histopathologic analysis 3,4,9,10,12,30,31,36 suggesting that these tumors arise within the hyperplastic ICC. In our study, the tumor nodules appeared to arise from a background of a hyperplastic Auerbach's plexus in the small bowel (Figs.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, GIST kindreds reported to date have been described to have primary GISTs arise from the small intestine 3,9,10,12,13,31,32,37,38 or the small intestine and the stomach 12,13,30,36,39 but not the stomach alone. On the other hand, studies have demonstrated that nearly two-thirds of all sporadic GISTs arise in the stomach.…”
Section: Discussionmentioning
confidence: 99%